Liquid Crystals for IR: Part III - Bi- and multicomponent mixtures based on perfluoroalkyl or perfluoroalkoxy terminated oligophenyls and tolanes. Issue 14 (7th December 2020) - Kula, Przemysław; Czerwiński, Michał; Herman, Jakub; Harmata, Piotr
ABSTRACT: Nine bicomponent systems have been prepared in order to check the ability of maintaining liquid crystalline properties of newly synthesised non-mesomorphic compounds shown previously (part I and part II) with compound having broad temperature range of nematic phase. Based on this study, several multicomponent mixtures has been developed. Their mesomorphic and spectral properties as well as birefringence, dielectric anisotropy and viscosity have been investigated. All of prepared mixtures are characterised by a wide transparency in MWIR region. Two multicomponent mixtures with different sign of dielectric anisotropy exhibit a very broad temperature range of nematic phase with the melting point below −10°C, birefringence value above 0.2, dielelectric anisotropy values above 2.0 and viscosity values below 77 mPa*s. GRAPHICAL ABSTRACT: uf0001